Varied Presentation of Nonvenereal Genital Dermatoses in Female: Report of Six Cases - Seema Rani; Anjali Dhiman; Sweta Singh; Purnima Malhotra (Journal of Dermatology and Dermatologic Surgery)
Genital disorders are not always sexually transmitted. Such nonvenereal genital dermatoses may be confined to the genitalia only or may also involve other body parts. There are many symptomatic as well as asymptomatic nonsexually transmitted diseases in female with atypical presentation. We are reporting the uncommon presentation of common entities in female reports of 6 cases.